Disembowelment following unsafe home delivery: Young life lost!. (January 2017) - Godara, Rajesh; Garg, Pradeep; Verma, Surender; Gupta, Sandhya
Injuries to the bowel are seldom reported. Yet these pose serious problems associated with uterine perforation during deliveries that take place outside of hospitals. This is also true for abortions that are performed illegally in developing countries by persons without any medical training. This case study is about a 20 years old girl who lost her life following an unsafe delivery at home. To avoid morbidity and mortality associated with unsafe deliveries, it is necessary to understand the scope of this problem and the factors related to it: governments, nongovernmental organizations, religious groups and women groups.